A model of influences of environmental stakeholders on strategic information systems planning success in an enterprise - Hovelja, Tomaz; Vasilecas, Olegas; Rupnik, Rok (Technological and Economic Development of Economy, 2013)
Worldwide spending of enterprises on information technologies (IT) in 2011 is projected to total USD 2.6 trillion with 350 enterprises each investing more than USD 1 billion. Despite such large and rapidly growing investment figures, the success rates of IT deployment projects over the past 20 years remained relatively low: approximately half of IT deployment projects were unsuccessful. Literature review reveals that inadequate strategic information system planning (SISP) is one of the main reasons for low deployment success rates of IT deployment projects and, thus, one of the current critical IT management issues. For this reason researchers and practitioners in the SISP field are currently directing their efforts into expanding the traditional understanding of SISP as a pure IT planning activity. In addition to the activities dedicated to the planning of IT investments, new SISP models should also include the contextual activities that enable adaptation of the deployed IT to the environment and knowledge transfer from the environment. In this paper, the authors propose an extended SISP model that includes influences of environmental stakeholders. The developed SISP model was empirically tested on a sample from the population of 1000 largest enterprises in Slovenia. The authors believe that the findings of their research and the suggested extended SISP model will improve understanding of SISP success factors in enterprises and consequently enable them to manage their IT investments with greater success.